The Need for Problem-Based Learning to Increase Self-Control in Islamic Education Learning in High School - Farida Saifulloh; Sudiyanto Sudiyanto; Mohammad Muchtarom (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
Self-control is one of the skills that is needed in the 21st century. Self-control affects students' skills in solving social environmental cues. The main foundation that gives strength to fend off external and internal bad things is the ability to control oneself. Student-oriented learning methods can increase the various abilities of students. The purpose of this study was to identify Problem-Based Learning as a learning method needed to improve self-control abilities in Islamic religious studies in high school. This research method is qualitative research with data collection procedures, data presentation, data reduction, and conclusions. Data were collected using three research instruments, namely observation, questionnaires, and inter-view guidelines. The results of the study show that: 1) The learning method that has been used in Islamic Education learning in high school, namely the expository method and students' self-control is low, 2) The learning method needed to increase student self-control in Islamic Education learning in high school is Problem-Based Learning, which is indicated by the duration of 135 minutes of study hours per week, the characteristics of Islamic Education subject that is relevant to the realities of life and train students to have good morals, the poor quality of Islamic Education Subject with an average learning outcome of 61.55, and 3) Learning methods that can improve students’ self-control in Islamic Education learning in high school is Problem-Based Learning by the character values that are formed in this method.